Imbalance of Microbacterial Diversity Is Associated with Functional Prognosis of Stroke - Xintong Zhang; Xiangyu Wang; Hong Zhao; Risheng Cao; Yini Dang; Binbin Yu (Neural Plasticity)
Objectives. There is mounting evidence to suggest that the pathophysiology of stroke is greatly influenced by the microbiota of the gut and its metabolites, in particular short-chain fatty acids (SCFAs). The primary purpose of the study was to evaluate whether the levels of SCFAs and the gut microbiota are altered in poststroke patients and to examine the relationship between these alterations and the physical condition, intestinal health, pain, or nutritional status of patients. Methods. Twenty stroke patients and twenty healthy controls were enrolled in the current study, and their demographics were matched. Gas chromatography was used to determine the fecal SCFAs, and 16S rRNA gene sequencing was used to evaluate their fecal microbiota. Microbial diversity and richness were examined using the diversity indices alpha and beta, and taxonomic analysis was utilized to determine group differences. The relationships between the gut microbiome and fecal SCFAs, discriminant bacteria, and poststroke clinical outcomes were analyzed. Results. Less community richness (ACE and Chao) was observed in the poststroke patients (P<0.05), but the differences between the poststroke group and the healthy control group in terms of species diversity (Shannon and Simpson) were not statistically significant. The makeup of the poststroke gut microbiota was distinct from that of the control group, as evidenced by beta diversity. Then, the relative abundances of the taxa in the poststroke and control groups were compared in order to identify the specific microbiota changes. At the level of phylum, the poststroke subjects showed a significant increase in the relative abundances of Akkermansiaceae, Fusobacteriota, Desulfobacterota, Ruminococcaceae, and Oscillospirales and a particularly noticeable decrease in the relative abundance of Acidobacteriota compared to the control subjects (P<0.05). In regard to SCFA concentrations, lower levels of fecal acetic acid (P=0.001) and propionic acid (P=0.049) were found in poststroke subjects. Agathobacter was highly correlated with acetic acid level (r=0.473, P=0.002), whereas Fusobacteria (r=−0.371, P=0.018), Flavonifractor (r=−0.334, P=0.034), Desulfovibrio (r=−0.362, P=0.018), and Akkermansia (r=−0.321, P=0.043) were negatively related to acetic acid levels. Additionally, the findings of the correlation analysis revealed that Akkermansia (r=−0.356, P=0.024), Desulfovibrio (r=−0.316, P=0.047), and Alloprevotella (r=−0.366, P=0.020) were significantly negatively correlated with high-density lipoprotein cholesterol. In addition, the Neurogenic Bowel Dysfunction score (r=0.495, P=0.026), Barthel index (r=−0.531, P=0.015), Fugl-Meyer Assessment score (r=−0.565, P=0.009), Visual Analogue Scale score (r=0.605, P=0.005), and Brief Pain Inventory score (r=0.507, P=0.023) were significantly associated with alterations of distinctive gut microbiota. Conclusions. Stroke generates extensive and substantial alterations in the gut microbiota and SCFAs, according to our findings. The differences of intestinal flora and lower fecal SCFA levels are closely related to the physical function, intestinal function, pain, or nutritional status of poststroke patients. Treatment strategies aimed at modulating the gut microbiota and SCFAs may have the potential to enhance the clinical results of patients.